Structural and morphological properties of in-situ biosynthesis of biocompatible bacterial cellulose/Laponite nanocomposites - Domeneguetti, Rafael R. [UNESP]; Sakai, Vanessa Y.; Perotti, Gustavo F.; Silva, Isabel C. [UNESP]; Tercjak, Agnieszka; Barud, Hernane S.; Pavan, Fernando [UNESP]; Constantino, Vera R.L.; Ribeiro, Sidney J. [UNESP] (Elsevier, 2023)
Bacterial cellulose (BC) membranes were produced in culture media containing Komagataeibacter xylinus microorganism and four different concentrations of Laponite (Lap) XLG up to 1.0% (m/v) to evaluate the availability of in-situ method for production of BC/Lap nanocomposites. The effect of Lap on the structure and some properties of the biosynthesised polymer was evaluated by thermogravimetric analysis coupled to mass spectrometry (TGA-MS), Fourier Transform infrared (FT-IR) and Raman (FT-Raman) vibrational spectroscopies, X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS) and atomic force microscopy (AFM). TGA-MS and vibrational spectroscopy indicated that Lap particles were not incorporated into the BC membranes using 0.10 or 0.25% of the inorganic phase whereas all obtained results showed that its presence had a strong influence on the BC properties. This result can be an effect of the interaction of hydrophilic Lap particles with elementary fibrils of cellulose, expelled from the bacteria, fostering the disruption of chains organization. However, the 3D hierarchical organization of BC at the microscale was not collapsed according to SEM and AFM images. As the amount of Lap increased in the culture medium and in the produced membrane, the ribbons became less defined, suggesting the predominance of thinner ribbons. The transparency of the membranes was enhanced when the nanoclay loading was raised. The presence of high clay loadings in the BC/Lap nanocomposite did not negatively impact the cell viability against keratinocytes in comparison to pristine BC membranes, opening new opportunities to explore such nanocomposites for biomedical, pharmaceutical and cosmetics uses.
Keywords: Biopolymers; Biosynthesised nanocomposite; Cellulose-synthesizing bacteria; Hectorite; Layered magnesium silicate; Polymer-clay nanocomposites